Reorienting Legal Protection of Employment in Indonesia in Facing Globalization and Digitalization - Topan Ahmad Anhari Harahap; Cita Suci; Anisa Dwi Putri; Abdillah Tarigan (ISNU Sumatera Utara, 2026)
The rapid development of globalization and digitalization has fundamentally transformed employment relations in Indonesia. Conventional employment patterns characterized by stable and formal work arrangements have increasingly shifted toward flexible and precarious forms of employment, particularly with the rise of the digital economy and platform-based labor. This transformation poses significant challenges to the existing labor law framework, which was originally designed to regulate permanent and formal employment relationships. As a result, many platform and gig economy workers are excluded from normative labor protections, including social security, wage protection, and job security, due to their classification as independent contractors or partners rather than employees. Labor law serves a strategic function as a protective instrument for workers, who are generally in a weaker bargaining position compared to employers. Within the welfare state paradigm, such protection is intended not only to provide legal certainty but also to promote social justice and societal welfare. However, the dynamics of globalization and digitalization have exposed a regulatory gap between evolving employment practices and existing legal norms, potentially weakening the protection of workers’ rights. This study applies a qualitative research method using a normative-juridical approach. Data were collected through a systematic review of labor law regulations and relevant legal literature and analyzed descriptively and qualitatively. The study emphasizes the urgent need to reorient Indonesian labor law policies to balance economic growth, investment interests, and the constitutional obligation to ensure equitable legal protection for all workers, particularly those in digital and non-standard employment relationships.